2019
DOI: 10.1007/s11356-019-04543-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of secondary metabolites produced by different cyanobacterial populations on the freshwater zooplankters Brachionus calyciflorus and Daphnia pulex

Abstract: Cyanobacterial blooms in eutrophic water bodies are a worldwide problem. Combined effects of mixtures of secondary metabolites produced by different cyanobacterial species on aquatic fauna are still not well recognised. We compared the survivorship of Brachionus calyciflorus Pallas (Rotifera) and Daphnia pulex Leyding (Cladocera) exposed to pure microcystin LR (MC-LR), anatoxin-a (ANTX) and to five extracts obtained from bloom-forming cyanobacteria Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 59 publications
1
27
0
1
Order By: Relevance
“…Deleterious effects in organisms belonging to aquatic fauna were also linked to APs production and other cyanopeptides [ 123 , 124 , 125 ]. The negative impact of these metabolites can partially justify the substitution of large-bodied zooplankton by small-bodied species during the blooming process since they affect differently these living beings [ 126 , 127 ]. The absorption of such molecules can occur by ingestion of cyanobacteria or through uptake of water.…”
Section: Ecologymentioning
confidence: 99%
“…Deleterious effects in organisms belonging to aquatic fauna were also linked to APs production and other cyanopeptides [ 123 , 124 , 125 ]. The negative impact of these metabolites can partially justify the substitution of large-bodied zooplankton by small-bodied species during the blooming process since they affect differently these living beings [ 126 , 127 ]. The absorption of such molecules can occur by ingestion of cyanobacteria or through uptake of water.…”
Section: Ecologymentioning
confidence: 99%
“…Species of the genus Microcystis affect both the phytoplankton community itself, due to the deterioration of illumination and the zooplankton and ichthyofauna, due to the release of toxins and changes in pH [75]. The reaction of Daphnia to toxins of blue-green algae is species-specific [76]. Experimental and field studies have shown that Daphnia thrives in the presence of green algae, cryptophytes, chrysophytes, or diatoms [77][78][79].…”
Section: Species Composition and Quantitative Variablesmentioning
confidence: 99%
“…Cyanobacteria constitute a diverse and widely distributed group of Gram-negative prokaryotes, found in freshwater, marine environments, and even terrestrial habitats [ 16 ]. They are well known to produce harmful toxins, but also a huge variety of secondary metabolites [ 16 , 17 ]. In fact, the cyanobacterial compound dolastatin 10 inspired the FDA-approved brentuximab vedotin for the treatment of soft carcinoma [ 18 ].…”
Section: Introductionmentioning
confidence: 99%